2019
DOI: 10.5812/compreped.80846
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Study on Pediatric Triage Decision-Making Power in Nurses and Nursing Students: A Cross Sectional Study

Abstract: Background: Triage nurses are the first people in the emergency department providing care to patients. Their knowledge is very important in efficient triage. According to the few studies on the factors affecting triage, the current study aimed at investigating the nurses and nursing students' knowledge about the triage of children. Objectives: Accordingly, the current study aimed at determining the level of knowledge of nursing students and nurses about pediatric triage and the impact of knowledge on the triag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…In the present study, the triage training course was identified as the predictor of TDM in ED nurses and EMTs. Several studies have reported that training is the foundation of a triage system and greatly contributes to TDM [12,28,29,37]. The results of this study were in line with those of previous studies [13,23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the triage training course was identified as the predictor of TDM in ED nurses and EMTs. Several studies have reported that training is the foundation of a triage system and greatly contributes to TDM [12,28,29,37]. The results of this study were in line with those of previous studies [13,23].…”
Section: Discussionsupporting
confidence: 92%
“…The results also showed that the levels of nursing proficiency and work experience were a predictor of TDM in ED nurses and EMTs. Experience and expertise have been reported as the most important factors influencing the decision of triage nurses [3,[27][28][29]. Studies show that expert nurses in the clinical decision-making process, using macro cognition, use various factors such as new information, environment, and organizational factors.…”
Section: Discussionmentioning
confidence: 99%
“…This also can be supported by Shehab et al (2017) and El-Guindy et al ( 2022) who reported that total triage knowledge among studied nurses showed marked improvement posttest in comparison to pretest assessment (29,30) . Furthermore, those findings concurred with Moirangthem (2019) who found that more than half of nurses had average level of knowledge about triage (31) , this can be supported by Pouy et al (2019) who revealed that most of the nurses did not have enough knowledge related to triage (32) . On the contrary side, the current study did not match the findings of Ina Lea etal (2022), who stated that more than half of nurses had good knowledge of triage, nearly half had moderate knowledge, and none had poor knowledge (33) .…”
Section: Figure (3): Correlation Between Total Nurses' Knowledge and ...supporting
confidence: 82%
“…In the same line Malakeh et al (2022) found that there was a positive correlation between triage knowledge and emergency experience (38) . In contrast to, Pouy et al (2019) who found no significant correlation between work experience and level of nurses' knowledge related to triage (32) . Also, Mustafa et al (2019) mentioned that there was no statistically significant correlation between nurse's knowledge, and their experience years (19. This could be due to a lack of ongoing educational training in pediatric emergency triage.…”
Section: Figure (3): Correlation Between Total Nurses' Knowledge and ...mentioning
confidence: 69%
“…According to a cross-sectional study, nurses and nursing students should undergo comprehensive training and reinforcement to acquire proficient triaging skills [ 5 ]. A systematic review revealed a notable paucity of research on evaluating pediatric triage tools in low- and middle-income countries (LMICs) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%